Antecedents of Organizational Commitment That Influence Teacher Job Performance - Apul Tumanggor; Unggul Kustiawan (HK-Publishing, 2022)
Abstract:This study aimed to examine the antecedents of organizational commitment, work environment, job stress, leadership empowering, and organizational commitment that affect teacher job performance. This research contributed to the scientific repertoire for organizational leaders and policymakers for educational institutions to improve teacher performance. Subjects of the research were teachers at private Catholic high schools totaling 200 people who had worked for more than 2 years in Jakarta, Indonesia. The survey used a purposive sampling method and data analysis using factor analysis and structural equation modeling. The results showed that the work environment and empowering leadership affected the organizational commitment, which has a significant positive effect on teacher job performance. On the other hand, job stress hurts organizational commitment. The competence of school leaders was urgent to be improved following the needs of stakeholders and the challenges of the times.Keywords: work environment, job stress, leadership empowering, organizational commitment, job performance. AbstrakPenelitian ini bertujuan untuk menguji anteseden komitmen organisasi, lingkungan kerja, stres kerja, pemberdayaan kepemimpinan, dan komitmen organisasi yang mempengaruhi kinerja guru. Penelitian ini memberikan kontribusi bagi khasanah keilmuan bagi pimpinan organisasi dan pengambil kebijakan bagi lembaga pendidikan untuk meningkatkan kinerja guru. Subjek penelitian ini adalah para guru di SMA Katolik swasta yang berjumlah 200 orang yang telah bekerja lebih dari 2 tahun di Jakarta, Indonesia. Survei menggunakan metode purposive sampling dan analisis data menggunakan analisis faktor dan pemodelan persamaan struktural. Hasil penelitian menunjukkan bahwa lingkungan kerja dan kepemimpinan yang memberdayakan berpengaruh terhadap komitmen organisasi yang berpengaruh positif signifikan terhadap prestasi kerja guru. Di sisi lain, stres kerja merusak komitmen organisasi. Kompetensi pemimpin sekolah sangat mendesak untuk ditingkatkan mengikuti kebutuhan pemangku kepentingan dan tantangan zaman.Kata kunci: lingkungan kerja, stres kerja, pemberdayaan kepemimpinan, komitmen organisasi, prestasi kerja.